factorise the following equation: x³+1/x³-2
Answers
Answered by
1
Step-by-step explanation:
Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).Q12. If p(x)=x²-4x+3, evaluate p(2)-p(-1).
Similar questions
Accountancy,
1 month ago
Accountancy,
3 months ago
Geography,
3 months ago
Physics,
11 months ago
Science,
11 months ago